Студентство України в радянських антирелігійних кампаніях 1920-х рр. - Рябченко, О. Л. (НТУ "ХПІ", 2014)
У статті, на основі широкого кола джерел, висвітлюються питання запровадження нової революційної обрядовості в студентському середовищі і в суспільстві в цілому. Студенти розглядаються як об'єкт і суб'єкт здійснення державної політики у відношенні до релігії. Визначені методи і форми боротьби з релігійними святами і обрядами та реакція на утвердження нової обрядовості в суспільстві.

In the article on the basis of a wide range of sources the problem of introduction of the revolutionary rites into the students community and society on the whole is considered. Everyday life of Ukrainian society is characterized by ambiguous processes associated with changes of moral values and goals in the Soviet society. The State discredited the eternal traditions imposed new rules of social life. In this study students are treated as an object and subject of the state policy with respect to religion. Anti-religious propaganda became an important component of the educational institutions activities, youth was seen by the power as an object for implementation of the new non-religious everyday life. Methods and forms of fighting with anti-religious holidays and rituals as well as reaction to strengthening of new rituals in the society are defined.
Ukraine students in the anti-religious campaigns of the 1920-th
Keywords: студенти; релігійна свідомість; радянські революційні свята; безбожна пропаганда; антицерковні кампанії; students; religious consciousness; Soviet revolutionary holidays; anti-religious propaganda; anti-clerical campaign